Methods in microbiology. - Mayer, Frank (Methods in microbiology ;, 1988)
This volume of this acclaimed series deals with electron microscopic techniques applied for the elucidation of microbial structures and structure-function relationships at cellular, sub-cellular, and macromolecular levels. Many of the recent findings on ultrastructural features of microorganisms have been obtained with newly developed methods, though classical approaches have not lost their validity. Therefore, both conventional and new methods have been incorporated into this volume. The topics dealt with are meaningful not only in bacterial cytology but also in physiology, enzymology, biochemistry, and molecular biology, and include aspects of medical and biotechnological application.